(untitled) (Asian Journal of Pharmaceutical and Health Sciences, 2012)
Matricaria chamomilla is in use for last many years as herbal remedy in various countries it is a well known herbal plant in ancient Egypt, Greece, and Rome. The chamomile drug is included in the Pharmacopoeia of 26 countries. The present study was focused on the characterization of the main constituents of Chamomile essential oil, its antioxidant property and antimicrobial activity. The essential oil and plant extracts was extracted by Clevenger apparatus and by Soxhlet apparatus respectively with various solvents. The compound analysis of Chamomile essential oil was analysed by Gas chromatographic technique. After component analysis the antioxidant activity of methanolic extract was performed using DPPH assay. The antibacterial assays were carried out by the disc-diffusion in order to determine the antibacterial activity of oil against the strains Bacillus subtilis (ATCC 10707), Escherichia coli (ATCC 0157:H7), Proteus vulgaris (MTCC 426), and Pseudomonas aeruginosa (ATCC 27853). This oil was found as a good source of á-bisabolol oxides A and chamazulene which are primarily responsible for antioxidant activity and antimicrobial activity of this essential oil.